2020
DOI: 10.1155/2020/9810709
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Molecular Mechanisms of the Effects of Prunella vulgaris against Subacute Thyroiditis Based on Network Pharmacology

Abstract: Prunella vulgaris (PV) has a long history of application in traditional Chinese and Western medicine as a remedy for the treatment of subacute thyroiditis (SAT). This study applied network pharmacology to elucidate the mechanism of the effects of PV against SAT. Components of the potential therapeutic targets of PV and SAT-related targets were retrieved from databases. To construct a protein-protein interaction (PPI) network, the intersection of SAT-related targets and PV-related targets was input into the STR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Inhibition of PDK3 activity or expression levels increases mitoROS, oxidative phosphorylation, and pyruvate dehydrogenase activity under normoxic conditions ( Kluza et al, 2012 ). Other pharmacology and molecular docking analyses have revealed that P. vulgaris (in both plant and prepared medicine forms) affects HIF-1α and the apoptosis signaling pathway in sleep disorders ( Guo et al, 2020 ), thyroiditis ( Shen et al, 2020 ), and diabetes mellitus ( Jiao et al, 2021 ). Moreover, UA and its derivatives have been trialed as HIF-1α inhibitors with anticancer potential ( Shan et al, 2016 ; Wang et al, 2016 ; Chi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PDK3 activity or expression levels increases mitoROS, oxidative phosphorylation, and pyruvate dehydrogenase activity under normoxic conditions ( Kluza et al, 2012 ). Other pharmacology and molecular docking analyses have revealed that P. vulgaris (in both plant and prepared medicine forms) affects HIF-1α and the apoptosis signaling pathway in sleep disorders ( Guo et al, 2020 ), thyroiditis ( Shen et al, 2020 ), and diabetes mellitus ( Jiao et al, 2021 ). Moreover, UA and its derivatives have been trialed as HIF-1α inhibitors with anticancer potential ( Shan et al, 2016 ; Wang et al, 2016 ; Chi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol, one of the active compounds in TFDM, is also an essential ingredient in the extracts of Ginkgo biloba leaves, having antioxidant properties by acting as a free radical scavenger ( Ahlemeyer and Krieglstein, 2003 ). Kaempferol plays a role in the regulation of inflammation and apoptosis through the targeting of the PI3-kinase p110-gamma subunit (PIK3CG) ( Shen et al, 2020 ). Luteolin, another active ingredient of TFDM, displays neuroprotective effects on the BBB by inhibiting fibrillary Aβ 1–40 -induced inflammation through the inhibition of the p38 MAPK signaling pathways, as reported by our previous work ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The network was composed of dots and lines. The nodes represent active ingredients, targets, or pathways, and the lines represent the interaction between them [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we adopted network pharmacology analysis based on bioinformatics and systems biology to carry out the research [ 13 ]. Network pharmacology systematically reveals the complex relationship between drugs and diseases by constructing biological networks and visualizing the network to analyze potential active ingredients, pivotal targets, signaling pathways, and diseases [ 14 ]. It is a powerful tool to improve drug efficacy and accelerate drug research and development.…”
Section: Introductionmentioning
confidence: 99%